The Platelet-To-Albumin Ratio and the Mean Platelet Volume-To-Albumin Ratio as Predictors of Disease Severity and Mortality in Pediatric Sepsis Patients - Okky Hudaya; Lucky Andriyanto; Arie Utariani (Indonesian Health Journal, 2026)
Pediatric sepsis remains a critical emergency condition with high morbidity and mortality rates, particularly in low- and middle-income countries. Early identification of patients at risk of severe outcomes is essential to guide timely interventions. This study aimed to evaluate the prognostic value of Platelet-to-Albumin Ratio (PAR) and Mean Platelet Volume-to-Albumin Ratio (MAR) in predicting disease severity and 7-day mortality among pediatric sepsis patients in the emergency room. A retrospective observational study was conducted on 101 pediatric patients admitted to Dr. Soetomo Hospital, Surabaya, from January 2020 to January 2025. PAR and MAR were measured on days 1, 3, and 5, and severity was assessed using PELOD-2 scores. Statistical analyses included ROC curves, Spearman correlations, and Kruskal–Wallis tests. Results demonstrated that MAR consistently showed superior predictive performance compared to PAR, with AUC values improving from 0.711 on day 1 to 0.905 on day 5, and significant correlations with PELOD-2 scores (p<0.001). PAR showed limited and inconsistent predictive ability. The findings indicate that MAR is a reliable and practical biomarker for early risk stratification and monitoring of pediatric sepsis severity. Future research should validate MAR in multicenter prospective studies and explore its integration with clinical scoring systems for enhanced prognostic accuracy.